2006
DOI: 10.1095/biolreprod.105.048579
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Phospholipase A2 Group IVA (PLA2G4A) Is Upregulated by Human Chorionic Gonadotropin in Bovine Granulosa Cells of Ovulatory Follicles1

Abstract: Prostaglandins are required for the ovulatory process, and their biosynthesis depends on the initial release of arachidonic acid from membrane phospholipids. We hypothesized that phospholipase A2 group IVA (PLA2G4A) expression is upregulated in granulosa cells (GC) at ovulation. We have characterized bovine PLA2G4A cDNA, and investigated its spatiotemporal regulation at the mRNA and protein levels in hCG-induced ovulatory follicles and in vitro, using forskolin-stimulated GC. Regulation of PLA2G4A mRNA express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 62 publications
2
28
0
Order By: Relevance
“…Furthermore, previous studies have shown that PACAP increases the production of progesterone and PGE2 in the ovary of crested newt, Triturus carnifex (Zhong & Kasson 1994, Gobbetti et al 1997, Gras et al 1999, Ko et al 1999. In the present work, we used primary granulosa cell cultures that have been previously established as a valuable in vitro model to study the regulation of several bovine genes, including PGHS-2 and cPLA2, and the production of PGE2 recapitulating results observed in vivo (Liu et al 1999, Sayasith et al 2004, Diouf et al 2006. A similar in vitro model was employed in rodents to study the gonadotropin-dependent regulation of PACAP and its role in the suppression of follicle apoptosis (Lee et al 1999.…”
Section: Discussionsupporting
confidence: 69%
“…Furthermore, previous studies have shown that PACAP increases the production of progesterone and PGE2 in the ovary of crested newt, Triturus carnifex (Zhong & Kasson 1994, Gobbetti et al 1997, Gras et al 1999, Ko et al 1999. In the present work, we used primary granulosa cell cultures that have been previously established as a valuable in vitro model to study the regulation of several bovine genes, including PGHS-2 and cPLA2, and the production of PGE2 recapitulating results observed in vivo (Liu et al 1999, Sayasith et al 2004, Diouf et al 2006. A similar in vitro model was employed in rodents to study the gonadotropin-dependent regulation of PACAP and its role in the suppression of follicle apoptosis (Lee et al 1999.…”
Section: Discussionsupporting
confidence: 69%
“…In all cases, quantification of PGs and their metabolites in follicular fluid during the preovulatory interval will be required to demonstrate the activity of PGDH to confirm its putative involvement in ovulation. Gonadotropin-induced expression of phospholipase A2 (cPLA2), the enzyme that mobilizes plasma membrane arachinodic acids for PGHS-2, PGHS-2, and PGES, terminal enzyme for PGE2 synthesis, is well documented in granulosa cells of preovulatory follicles (Sirois 1994, Sirois & Doré 1997, Filion et al 2001, Diouf et al 2006. Our recent studies also have shown that aldo-keto reductase 1C23 (AKR1C23), a multifunctional enzyme believed to possess PGFS-like activity for PGF2a production, is induced by hCG in equine preovulatory follicles (Brown et al 2006).…”
Section: Discussionmentioning
confidence: 96%
“…The present study describes hCG-dependent up-regulation of AD-AMTS1 in bovine preovulatory follicles in vivo before follicular rupture and documents the fact that a similar temporal up-regulation of ADAMTS1 could be replicated in vitro by forskolin in primary cultures of bovine granulosa cells, thus establishing the value of the cell culture system for further studying the transcriptional control of ADAMTS1 gene expression in bovine preovulatory follicles. Forskolin was used in vitro instead of LH or hCG to avoid issues related to variations in LH receptor expression in granulosa cells maintained in cultures and because of its demonstrated ability to replicate in vitro the gonadotropin-dependent regulation of a number of ovulatory genes observed in vivo in bovine granulosa cells (23)(24)(25)(37)(38)(39)(40)(41). Importantly, this study unravels for the first time some of the molecular mechanisms involved in the regulation of ADAMTS1 in granulosa cells of a large monoovulatory species.…”
Section: Discussionmentioning
confidence: 99%